The use of technological tools in fish production: a systematic literature review - Rojas-Molina, Lynda Yaneth; Tique-Pinto, Víctor Hugo; Bocanegra-García, José Joaquín (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
Fish farming is a fundamental economic area for several communities. Traditionally, the processes inherent to this activity, such as fish feeding, marking, reproductive behavior and parental care are done manually; however, in recent years, some fish farmers have incorporated technological tools in process automation. This systematic literature review describes some of the tasks related to fish farming where technological tools have been applied. Some of these activities involve the recognition and control of water physical and chemical variables, water levels regulation, and fish feeding. The study suggests new opportunities for application of technologies, particularly low-cost technologies, because they are accessible to the largest number of farmers and their use guarantees the process improvement. The study also highlights the importance of using alternative energies in order to protect natural resources and minimize the environmental impact.